Increased lipid oxidation during exercise in obese pubertal girls: A QUALITY study. (2nd December 2013) - Jabbour, Georges; O'Loughlin, Jennifer; Sabiston, Catherine; Tremblay, Angelo; Mathieu, Marie‐Eve
<x xml:space="preserve">Abstract</x> Objective This study explores differences in LO rates between pre‐pubertal and pubertal girls of three body weight status groups. Methods The sample included 39 pre‐pubertal girls [12 normal‐weight (NW), 12 overweight (OW), and 15 obese (OB)] and 37 pubertal girls [16 NW, 10 OW, and 11 OB]. Following a rest period, the girls performed a graded maximal cycling test. The %LO contribution was computed at each stage. Results The %LO contribution did not differ between NW, OW, or OB pre‐pubertal girls at each exercise stage. In contrast, pubertal OB girls showed a statistically significantly higher %LO contribution at 25, 50, and 75 W stages compared with OW and NW as well as with OB pre‐pubertal girls. Conclusions Our results demonstrate that entering puberty is a period associated with differentiation in substrate selection in obese girls. A higher %LO contribution may help girls to solicit more fat while performing submaximal exercise.